(untitled) (Zoo Botanica, 2025)
Wheat is the staple food of Pakistan and plays an important role in national food security. Changing climatic conditions, receding land availability due to increasing population, deficit in irrigation water availability during wheat season, and increasing cost of inputs are among the factors that are constraints on sustainable wheat production. Under these conditions, conventional wheat production system may no longer ensure food security and profitability. The Cotton-wheat system is the most important cropping system and the prime source of food supply in Pakistan. A field trial was conducted at Agronomic Research Institute, Faisalabad using strip plot design for evaluation of environment friendly and economically feasible approaches for wheat production in cotton-wheat cropping system. Three sowing methods viz bed planting, ridge planting (broadcast augmented with furrow) and flat planting were tested under three tillage levels: zero tillage (relay wheat sowing), conventional tillage and minimum tillage. Results revealed that zero tillage (relay wheat sowing) performed the best out of all tillage options keeping in view the yield and economic returns. It was also the best option for CO2 emission reduction due to the elimination of fuel consumption (for land preparation and sowing). Sowing methods showed variable response for yield as flat sowing and bed planting performed better than ridge planting in relay crop, but ridge planting was on top in both conventional and minimum tillage. It was concluded that relay planting under bed and flat sowing was the best environment-friendly and economically viable approach for wheat production in cotton-wheat cropping system.